2014
DOI: 10.5603/piap.2014.0064
|View full text |Cite
|
Sign up to set email alerts
|

Mikobakterioza płuc. Rzadka choroba czy narastający problem epidemiologiczny?

Abstract: Mikobakterioza płuc. Rzadka choroba czy narastający problem epidemiologiczny? Non-tuberculous mycobacterial lung disease. Rare entity or emerging epidemiological problem? Praca nie była finansowana

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 24 publications
0
4
0
4
Order By: Relevance
“…The prevalence of pulmonary mycobacteriosis is still increasing. In the United States, it is currently higher than prevalence of tuberculosis [7].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The prevalence of pulmonary mycobacteriosis is still increasing. In the United States, it is currently higher than prevalence of tuberculosis [7].…”
Section: Discussionmentioning
confidence: 97%
“…Among 126 subjects with COPD who underwent surgical lung-volume reduction in two British hospitals, signs of NTM infections were detected in 10% of postsurgical histological mawww.journals.viamedica.pl terial [14]. Basing on population studies carried out in Denmark, the authors concluded that in patients with COPD, the risk of mycobacterial infection is 15 times higher, and in individuals with bronchiectasis -187 times higher in comparison with the general population [7]. In every group, the risk increased significantly when the subjects received corticosteroids, and was dose -dependent [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dla ludzi często są tylko saprofitami, kolonizują drogi oddechowe, przewód pokarmowy i układ moczowo-płciowy człowieka [1,2]. W grupach podwyższonego ryzyka zachorowania na mykobakteriozy znajdują się pacjenci z przewlekłymi chorobami płuc, takimi jak: rozstrzenie oskrzeli, mukowiscydoza, przewlekła obturacyjna choroba płuc (POChP), pylica, proteinoza pęcherzyków płucnych, po przebytej gruźlicy płuc, a także chorzy na cukrzycę, niewydolność nerek, nadciśnienie płucne oraz chorzy z upośledzeniem funkcji układu immunologicznego, między innymi: zakażeni ludzkim wirusem niedoboru odporności (HIV, human immunodefiwww.journals.viamedica.pl ciency virus), po przeszczepieniu szpiku kostnego lub narządów czy leczeni immunosupresyjnie z innych przyczyn [4][5][6][7].…”
Section: Wstępunclassified